Stories of accounting change during financial reform of public enterprises - Abu Kasim, Nor Aziah (Universiti Putra Malaysia Press, 2006)
This paper analytically compares five commercially-oriented public enterprises from different countries which were subjected to the process of accounting and organisational changes in order to become profitable. The five case studies were selected for their attention to the importance of context, and to the process of how and why accounting evolved, interpreted and used within specific organisations. A comparison of the insights drawn from these case stories allows some possible lessons to be learnt and parallels to be drawn. The comparison reveals that the process of organisational change through accounting is complex and may not always evolve as an influential and effective means of altering behaviour and accepted ways of thinking. One vital lesson is that accounting change is implicated with various other non-technical issues such as environmental pressures, culture or ways of thinking, power and trust.